Self-Fertilization, Inbreeding, and Yield in Alfalfa Seed Production - Dieterich Mabin, Molly E.; Brunet, Johanne; Riday, Heathcliffe; Lehmann, Lauren (Frontiers in Plant Science, 2021)
Selfing (self-pollination) is the ultimate form of inbreeding, or mating among close relatives. Selfing can create yield loss when inbreeding depression, defined as a lower survival and reproduction of inbred relative to outbred progeny, is present. To determine the impact of selfing in alfalfa (Medicago sativa L.), we quantified the selfing rate of 32 alfalfa seed-production fields located in three regions, the Pacific Northwest, the Central Valley and the Imperial Valley of California. Selfing rates (the proportion of selfed seeds) varied between 5.3 and 30% with an average of 12.2% over the 32 seed production fields. In both the parents and their progeny, we observed an excess of heterozygotes relative to Hardy-Weinberg expectations. We detected notable levels of inbreeding in parents (0.231 ± 0.007 parental inbreeding coefficient) and progeny (0.229 ± 0.005). There was a 15% decrease in the number of seeds per stem (seed set) and a 13% decline in the number of seeds per pod in selfed relative to outcrossed stems, but negligible inbreeding depression for pods per raceme and seed weight. The number of racemes on selfed stems increased significantly in fields with greater selfing rates, supporting the presence of geitonogamous or among flower selfing. Despite the significant level of inbreeding depression, seed set did not decrease in fields with higher selfing rates, where the greater number of racemes on the selfed stems increased seed set. The effects of field selfing rate on seed yield metrics were mostly indirect with direct effects of the number of racemes per stem. Available data indicate that the majority of selfing in alfalfa is pollinator-mediated and thus eliminating selfing in alfalfa seed production would require the selection of self-incompatible varieties, which, by eliminating inbreeding depression, would provide a 15% potential increase in seed yield and an increase in future hay yield.